(untitled) (Revista Direito em Debate, 2023)
This article analyzes Advisory Opinion nº 24 issued by the Inter-American Court of Human Rights (Inter-American Court) in relation to people belonging to the LGBTIQ movement (lesbian, gay, bisexual, transsexual, intersex and queer). An approach is made on the functioning of the Inter-American Court as well as on the concepts of the right to equality, gender identity and non-discrimination. The purpose of this essay is to demonstrate the influence that Advisory Opinion nº 24 of the Inter-American Court has in relation to Brazil. In this case, the Supreme Federal Court (STF) understood that it is possible to change the name and gender in the civil registry seat even without performing a sex reassignment surgical procedure. The adopted methodology was empirical through the analysis of the constitutive treaties and concrete cases. The conclusion of the essay is that the STF, in a clear dialogue with the Inter-American Court, harmonized its jurisprudence in relation to the Inter-American Court of Human Rights, avoiding in the case any international responsibility from Brazil.